Analisis faktor-faktor penghambat dalam pembelajaran membaca permulaan pada peserta didik kelas II sekolah dasar - Laetitia Sabrina Dewashanty; Retno Winarni; Joko Daryanto (Universitas Sebelas Maret, 2023)
This study aims to describe the results of the analysis of factors that hinder learning to read beginning and describe solutions for the process of learning to read beginning in class II students. This research uses descriptive qualitative research method. The subject of this research is the second grade teacher of SDIT IslamyCawas. Research data were collected through interview data collection techniques and document studies. The data analysis technique used the Miles and Huberman model. The results showed that the factors that hindered early reading learning were as follows: (1) The teacher did not prepare for learning in the classroom. (2) Student factors, difficulty concentrating during learning due to fatigue, being disturbed by friends, and hyperactivity. (3) Factors in the learning process, use of inappropriate learning methods, less varied learning resources, lack of learning media, and lack of interaction between teachers and students. (4) Factors of facilities and infrastructure, lack of reading resources, absence of libraries, teaching aids and available learning media are not adequate. (5) Environmental factors, a family environment that is not conducive for students and the lack of tutoring by parents due to economic demands. Solutions used by teachers: (1) Mentoring and special assignments for hyperactive students. (2) A special class for learning to read for students who have difficulty reading. (3) Looking for reading sources and learning media from the internet.